2015
DOI: 10.1186/s13065-015-0093-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, chemical and microbiological changes during fermentation of tarhana formulated with different flours

Abstract: BackgroundTarhana is a fermented cereal product that is used for the preparation of one of the favourite soups in Turkish cuisine. Tarhana is a mixture of wheat flour, yoghurt, baker’s yeast, salt, and various vegetables, spices and seasonings. It is obtained by mixing all ingredients in the recipe and afterwards the mixture is let to ferment at room temperature. Following fermentation tarhana is dried or frozen for long term storage. In this study, to improve the nutritional benefits of tarhana, whole wheat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 33 publications
2
15
0
3
Order By: Relevance
“…Tarhana zenginleştirilmeye açık bir gıdadır (Bilgiçli ve Ibanoglu, 2007). Kuru formuyla cips şeklinde veya sulandırılmış kuru tozun kaynatılmasıyla çorba şeklinde tüketilmektedir (Tamer vd., 2007;Kumral, 2015).…”
Section: Introductionunclassified
“…Tarhana zenginleştirilmeye açık bir gıdadır (Bilgiçli ve Ibanoglu, 2007). Kuru formuyla cips şeklinde veya sulandırılmış kuru tozun kaynatılmasıyla çorba şeklinde tüketilmektedir (Tamer vd., 2007;Kumral, 2015).…”
Section: Introductionunclassified
“…Previous studies on tarhana have predominantly been performed with dough containing yeast starter where the fermentation is only continued for 3-7 days. In one such study, Kumral (2015) observed that the gliadin bands obtained with 3-day fermented dough was visibly lighter than that of unfermented dough samples. It can be noted that the gluten content of BT and SS formulations both were reduced by 7% even by the 5 th day of fermentation.…”
Section: Gluten Contentmentioning
confidence: 99%
“…Traditional tarhana can be modified and formulated with different ingredients to improve its properties. It was prepared with lentil and chickpea (Türker and Elgün, 1995) Kumral, 2015). This study aimed to determine the functional, rheological and sensorial properties of tarhana prepared with different substitution ratios of whole cereal grains' (wheat, oat flakes and barley) meal.…”
Section: Introductionmentioning
confidence: 99%